2010
DOI: 10.1111/j.1600-0501.2010.02064.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of socket preservation therapies following tooth extraction in non-molar regions in humans: a systematic review

Abstract: Data concerning socket preservation therapies in humans are scarce, which does not allow any firm conclusions. Socket preservation may aid in reducing the bone dimensional changes following tooth extraction. However, they do not prevent bone resorption because, depending on the technique, on the basis of the included papers one may still expect a loss in width and in height.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
259
4
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(292 citation statements)
references
References 39 publications
19
259
4
10
Order By: Relevance
“…Many studies on ridge preservation have documented the structural changes that occur around the alveolar ridge following ridge preservation [13,[33][34][35]. It is well-known that ridge preservation can limit and delay alveolar bone alteration [36,37]. Not all studies have reported beneficial effects from reducing alveolar ridge atrophy [36,38] which implies that ridge atrophy occurs in almost all the extraction sockets regardless of ridge preservation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies on ridge preservation have documented the structural changes that occur around the alveolar ridge following ridge preservation [13,[33][34][35]. It is well-known that ridge preservation can limit and delay alveolar bone alteration [36,37]. Not all studies have reported beneficial effects from reducing alveolar ridge atrophy [36,38] which implies that ridge atrophy occurs in almost all the extraction sockets regardless of ridge preservation.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that ridge preservation can limit and delay alveolar bone alteration [36,37]. Not all studies have reported beneficial effects from reducing alveolar ridge atrophy [36,38] which implies that ridge atrophy occurs in almost all the extraction sockets regardless of ridge preservation. In this study, we reported negative postextraction remodeling changes (approximately 80% of original soft tissue volume) in all three groups after tooth extraction accompanied with ridge preservation (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Even thick-wall phenotypes exhibited bone loss of more than 1 mm, which could affect esthetics negatively. Efforts have been made to prevent these dimensional changes following tooth extraction, but neither immediate implant placement nor ridge preservation techniques were able to maintain the facial osseous architecture Ten Heggeler et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…5 Although the bone resorption continues over time after tooth extraction, during the first month, the most statistically significant loss of alveolar dimension occurs. 6 Alveolar ridge resorption can create a clinical problem in two different ways: one, for the fabrication of conventional or implant-supported prostheses, an esthetic problem is created and second, it can make dental implants placement very difficult or sometimes even impossible. Therefore, following tooth extraction preservation of alveolar bone dimensions is always desirable.…”
Section: Introductionmentioning
confidence: 99%